2023
DOI: 10.3389/fmars.2023.1058354
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic cod (Gadus morhua) assessment approaches in the North and Baltic Sea: A comparison of environmental DNA analysis versus bottom trawl sampling

Abstract: The assessment of fish stocks is often dependent on scientific trawl fisheries surveys, which are both invasive and costly. The analysis of environmental DNA (eDNA) from water samples is regarded as a non-invasive and cost-effective alternative, but meaningful performance evaluations are required for a wider application. The goal of this study was to comparatively analyze a newly developed, more sensitive real-time PCR based eDNA approach with bottom trawl fisheries catches to locally detect and quantify Atlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Similarly, a study of eDNA from four Atlantic salmon farms, raising adult fish, detected eDNA farther than 5 km from the nearest farm—consistent with the substantially larger biomass among the Atlantic salmon farms (Shea et al., 2022). More broadly, the relationship between biomass/abundance and eDNA concentration has been correlated with trawl catches (Kasmi et al., 2023; Maes et al., 2023; Salter et al., 2019), acoustic data (Shelton et al., 2022), beach seines (Shelton et al., 2019), and angling catches (Ogonowski et al., 2023). These studies generally identify a positive relationship between biomass and DNA concentration, presumably due to increased DNA shed by more individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study of eDNA from four Atlantic salmon farms, raising adult fish, detected eDNA farther than 5 km from the nearest farm—consistent with the substantially larger biomass among the Atlantic salmon farms (Shea et al., 2022). More broadly, the relationship between biomass/abundance and eDNA concentration has been correlated with trawl catches (Kasmi et al., 2023; Maes et al., 2023; Salter et al., 2019), acoustic data (Shelton et al., 2022), beach seines (Shelton et al., 2019), and angling catches (Ogonowski et al., 2023). These studies generally identify a positive relationship between biomass and DNA concentration, presumably due to increased DNA shed by more individuals.…”
Section: Discussionmentioning
confidence: 99%
“…When designed stringently and after thorough validation, these are highly reliable and often effectively linked to the biomass and abundance of the target organism (e.g. in Takahara et al, 2012;Doi et al, 2015;Lacoursière-Roussel et al, 2016;Yamamoto et al, 2016;Capo et al, 2019;Knudsen et al, 2019;Salter et al, 2019;LeBlanc et al, 2020;Brys et al, 2021;Fukaya et al, 2021;Shelton et al, 2022;Kasmi et al, 2023;Urban et al, 2023). Nowadays, the main technique used in species-specific detection of environmental samples is real-time quantitative PCR (qPCR).…”
Section: Targeted Ednamentioning
confidence: 99%
“…Studies also considering the different variables that may be having an influence on eDNA concentration (such as temperature or salinity) use linear mixed-effects models (Itakura et al, 2019) or generalized linear models (Thomsen et al, 2016;Tillotson et al, 2018;Knudsen et al, 2019). However, Kasmi et al (2023) found differences in the relationship between eDNA copies and biomass depending on the statistical methods, getting better results when using Gaussian Process Regression (GPR), neural network and non-linear regression model, than with simple regression models.…”
Section: Correlating Edna Concentration With Abundance or Biomassmentioning
confidence: 99%
See 2 more Smart Citations